Implications of Anomalous Crustal Provinces for Venus' Resurfacing History. Issue 10 (15th October 2020) - Karlsson, R. V. M. K.; Cheng, K. W.; Crameri, F.; Rolf, T.; Uppalapati, S.; Werner, S. C.
Abstract: Current Venus tectonics suggests a stagnant lid mode of mantle convection. However, the planet is debated to enter an episodic regime after long quiescent periods, driven by resurfacing due to rapid subduction and global crustal recycling. Tessera regions that cover approximately 10% of Venus' surface appear to be strongly deformed, which suggests that they have survived at least the latest resurfacing event, although the composition and age of the tesserae are unknown. Based on mantle convection modeling, we studied the effects of anomalous crustal provinces (ACPs) on mantle dynamics and postoverturn lithospheric survival. As a hypothesis, we assume ACPs to be thick, compositionally anomalous, and rheologically strong units, similar to terrestrial cratons. We model Venus with a varying number of preimposed ACP units and differing lithospheric yield stress in 2‐D and 3‐D spherical geometry. The impact of ACPs on mantle dynamics and the survival of lithosphere is investigated by examining the thermal evolution, crustal thickness, and surface age distribution. We find that the number and timing of overturns are highly dependent on the yield stress and, to some degree, on the number and size of the preimposed ACPs. ACPs in particular affect the wavelength of convection and may foster the survival of lithosphere even of those portions not being part of an ACP. However, ACPs do not seem to be a good analog for tessera regions due to their exaggerated age and (likely) thickness, but—with appropriate density contrast—may be more useful representatives of Venus' highland plateaus. Plain Language Summary: Plate tectonics shapes the Earth's surface but is currently probably not active on Venus. Instead, periods with a more mobile Venusian surface remain possible, in particular because the surface is rather young. Episodic resurfacing events—known as overturns—during which much of the surface is recycled into the planetary interior may explain this. However, about 10% of Venus' surface are covered by tesserae, strongly deformed and possibly older‐than‐average regions that may have survived overturns. The origin of such anomalous crustal provinces (ACPs) is unknown, but we hypothesize them to be similar to the cratonic keels of Earth's continental crust. We investigate how ACPs affect the interior dynamics and resurfacing history and whether they promote the (partial) survival of the surface during overturns. We find that both the presence of ACPs and the strength of the lithosphere alter the overturn frequency. ACPs affect the mantle flow pattern and facilitate survival of non‐ACP lithosphere and crust by shielding it from recycling during overturn events. After analyzing our model‐predicted distributions of crustal thickness and surface age, however, preexisting ACPs do not seem to be adequate analogues for Venus' tesserae, as their thickness and age appear exaggerated given the observation on Venus' surface. Key Points: Yield stress and the presence of ACPs alter the frequency of overturn events Survival of crustal material during overturn events changes with the presence of ACPs ACPs do not seem to be a good representation for Venus' tesserae regions